95.9k views
5 votes
Nathaniel is using the quadratic formula to solve 0 = x2 + 5x - 6. His steps are shown below. What are the solutions to the equation? x = –1, 6 x = –6, 1 x = –22, 27 x = –27, 22 Mark this and return

2 Answers

6 votes

Answer: Second Option is correct.

Explanation:

Since we have given that


x^2+5x-6=0

We need to calculate the solutions to the equation :

We will use "Split the middle terms" :


x^2+5x-6=0\\\\x^2+6x-1x-6=0\\\\x(x+6)-1(x+6)=0\\\\(x+6)(x-1)=0\\\\x+6=0;x-1=0\\\\x=-6,1

So, Second Option is correct.

User Madcow
by
5.2k points
3 votes
The quadratic equation is;
x²+5x-6 = 0
x²+6x-x-6 = 0
x(x+6)-1(x+6) = 0
(x+6)(x-1) = 0
So,
x+6 = 0 and x-1 = 0
x=-6 and x = 1
Thus the answer is
x = -6,1
User Nassim Assaf
by
5.6k points